Vocation of the Business Leader: A Reflection (selected texts) - Consejo Pontificio para la Justicia y la Paz, - (Cultura Económica, 2019)
Vocation of the Business Leader: A Reflection Selected texts from the document by the Pontifical Council for Justice and Peace (2012)